Rootfinding : An Iterative Tool to Solve Different Problems - Adhikari, Iswarmani (Himalayan Physics, 2015)
The aim of this paper is to apply the iteration methods for the solution of non-linear equations. Among the various root finding techniques, two of the common iterative methods Regula-falsi (false position) and the Secant method are used in two different problems to show the applications of numerical analysis in different fields.The Himalayan PhysicsVol. 5, No. 5, Nov. 2014Page: 121-125